Effects of a glyphosate-based herbicide in pejerrey Odontesthes humensis embryonic development. (October 2017) - Zebral, Yuri Dornelles; Costa, Patrícia Gomes; de Castro Knopp, Bruna; Lansini, Luize Real; Zafalon-Silva, Bruna; Bianchini, Adalto; Robaldo, Ricardo Berteaux
Abstract: Glyphosate-based herbicides (GBH) are the major pesticides used worldwide. Among them, the Roundup formulations are the most popular. Some aspects of GBH toxicity are well known, such as induction of oxidative stress. However, embryotoxicity is scarcely known. Therefore, the aim of the present study was to evaluate the effect of exposure to different Roundup Transorb R concentrations (0.36, 1.80, 3.62 and 5.43 mg glyphosate a.e./L) on Odontesthes humensis embryonic development. Embryos were sampled at three exposure times (48, 72 and 96 h). After 48 h, the stage of embryonic development and the number of somite pairs were analyzed; after 72 h, the percentage of pigmented embryos were evaluated and after 96 h, the eye diameter (ED) and the distance between eyes (DE) were measured. Mortality rates were daily calculated. Results show that Roundup exposure to all concentrations did not alter the endpoints evaluated at 48 and 72 h. On the other hand, exposure for 96 h to all concentrations induced a concentration-dependent reduction in ED and DE. Additionally, exposure to 5.43 mg a.e./L increased mortality. These findings indicate that Roundup has the potential to produce morphological alterations in fish embryos even at the lower and ecologically relevant concentration tested (0.36 mg a.e./L). This result corroborates the hypothesis that glyphosate alters the retinoic acid signaling pathway. Additionally, our findings indicate that exposure to high concentrations of Roundup (5.43 mg a.e./L) for 96 h causes high mortality rates of fish embryos. This is the first report of GBH embryotoxicity in an endemic fish of southern areas in South America. Highlights: Roundup exposure does not affect the stage of embryonic development in pejerrey. The number of somite pairs in pejerrey embryos is not influenced by Roundup. Roundup exposure does not affect pigmentation in pejerrey embryos. Environmentally relevant concentrations of Roundup induce craniofacial deformities. Exposure to non-realistic concentrations of Roundup induces embryonic mortality.